Photograph of Alexander Wheelock Thayer - E. Bieber (photographer)::::::::::::::: (Hamburg; Germany; E. Bieber, 2023)
Studio portrait photograph of Alexander Wheelock Thayer by E. Bieber in Hamburg, mounted on card with Bieber's imprint and address at "No. 20, Neuer Jungfernstieg" on front and back; from 1888 or later based on printed statement "Mitglied der Jury der internation. Ausstellung Brüssel 1888" on verso.